Missing energy estimate in the light of the muon discrepancy - Tueros, Matias Jorge (2013)
The determination of the primary energy of extensive air showers using the fluorescence technique requires an estimation of the energy carried away by the particles that do not deposit all their energy in the atmosphere. This estimation is typically made using Monte Carlo simulations and thus depends on the model predictions for neutrino and muon production. In this contribution we describe a new method that could be used to obtain the missing energy directly from events measured simultaneously with the fluo- rescence and the surface detectors of the Pierre Auger Observatory, based on a toy model of the shower cascade. The method is applied to a synthetic sample of events to show its robustness and we discuss how the results could be used to make an estimation of the number of high energy muons in the cascade.